The Principle of Prudence in Murabahah Financing: An Empirical Study at the LKMS MM Sejahtera Cooperative in Bengkulu City - Anwar Junaidi; Romi Adetio; Alzarah Maharani (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2023)
The purpose of this research is to determine the application of the precautionary principle in the distribution of murabahah financing in the LKMS MM Sejahtera cooperative, Bengkulu City. This research uses qualitative research methods. The results of the research show that in applying the precautionary principle, Cooperative Institutions analyze prospective customers based on the 5C principles, such as character, capacity, capital, collateral, and conditions of economy. The character principle involves examining the customer's credit history, direct surveys, and information from the Financial Information Services System (SLIK), while the capacity principle involves evaluating the customer's income, debt, and living expenses. The capital principle assesses the customer's capital, the collateral principle assesses the guarantee submitted by the customer, and the condition of economic principle assesses the customer's ability to pay installments. The MM Sejahtera LKMS Cooperative faces obstacles in applying the principle of prudence, especially related to the principle of colleteral or guarantee. Customers often have a guarantee that is less than the amount of financing submitted, so the cooperative cannot provide financing. To overcome this, cooperatives look for solutions by asking for additional guarantees from customers, or finding guarantors from the cooperative's internal environment